Self‐reporting and Market Structure. (25th February 2021) - Rablen, Matthew D.; Samuel, Andrew
Abstract : Many regulators utilize self‐reporting, that is, wrongdoers reporting their own crimes to the authority, to enforce regulations in a variety of market contexts. This paper studies the effectiveness of self‐reporting within the context of an oligopoly. We identify two important consequences of implementing self‐reporting (relative to no‐reporting) for a welfare‐maximizing regulator. First, if the regulator can control only the audit probability and fine, then whether compliance rises or falls upon implementing self‐reporting depends on the level of competition. Second, if the regulator can also control the market size, then the welfare‐maximizing policy entails self‐reporting but with more competition and lower compliance than under no‐reporting.